Forging the future of nanotechnology: embracing greener practices for a resilient today and a sustainable tomorrow - Parab, Ankita Rajendra; Ramlal, Ayyagari; Gopinath, Subash C. B.; Subramaniam, Sreeramanan (Frontiers in Nanotechnology, 2025)
Various chemical and physical methods have been proposed for the synthesis of nanoparticles (NPs). However, these methods have disadvantages, such as high energy loss and high capital requirements. To overcome these problems, alternative methods for NP synthesis, such as biological or green synthesis, are favoured to overcome these problems. Green synthesis of NPs is environmentally friendly, economical and non-toxic. This review examines the history of green synthesis, focusing on using environmentally friendly methods. The integration of machine learning into NP production and a range of NP applications in healthcare, disease treatment and the environment are also covered.